Vegetation Diversity in Nebkhas of Phog (Calligonum polygonoides L.) in the Thar Desert of India: RESEARCH PAPER - Anil Patidar,; J.P. Singh,; P. C. Moharana,; Mavji Patidar,; Saranya R.,; S.C. Meena,; Shiran K.,; R.S. Mehta, (Annals of Arid Zone, 2025)
Nebkhas are hillocks formed by the accumulation of wind-blown sediment within or around shrub canopies in arid and semi-arid landscapes. These landforms create distinct micro-environments that strongly influence vegetation diversity and spatial distribution. In the present study, we examined the size characteristics and vegetation diversity of nebkhas associated with the shrub Calligonum polygonoides in the Tanot region of Jaisalmer District, located in the Thar Desert of India. The nebkhas were oval to ellipsoidal in shape and ranged from 0.5 to 2.0 m in height, with an average height of 1.13 m. The height of C. polygonoides growing on these nebkhas varied between 1.0 and 2.8 m, with a mean of 2.2 m. A total of 11 plant species belonging to 8 families and 11 genera were recorded on the nebkhas. The grass Ochthochloa compressa emerged as the dominant species, exhibiting the highest Importance Value Index (IVI) of 70.9. The co-dominant species were Aristida spp. and Indigofera argentea with IVI values of 54.3 and 43.4, respectively; both were present in all sampled nebkhas. These were followed by Aerva javanica and Dipterygium glaucum. The findings highlight that conserving C. polygonoides in desert ecosystems plays a crucial role in maintaining associated plant  communities. Protection of this keystone shrub also supports the persistence of important desert species such as Aerva javanica, Leptadenia pyrotechnica, Panicum turgidum, Lasiurus scindicus, Ochthochloa compressa and Indigofera argentea.